Bacterial risk assessment in informally produced milk consumption in Côte d’Ivoire - Kouamé-Sina, S.M.; Yobouet, B.A.; Dadie, A.; Makita, K.; Grace, Delia; Dje, M.; Bonfoh, Bassirou (2011)
BACKGROUND: Fifteen dairy farms from five zones of Abidjan, Côte d’Ivoire, were characterized to assess the conditions of raw milk production and marketing, and detect whether Bacillus cereus presented a risk to the consumer. METHODS: In total, 119 udder milk, 113 udder skin swabs, 22 hand swabs of farmers, 14 mixture milk of shepherd, 14 utensils rinse water, 16 environment samples and water used to rinse material for milking in 5 farms were sampled. Three informal markets in these zones were visited and 17 retailer pooled milk samples were collected and analyzed. The isolated strains were characterized and their virulence genes were detected by polymerase chain reaction (PCR). Milk quality was determined by comparing the average count of B. cereus to the limits of acceptability. To assess the impact of the consumption of raw milk, a consumer survey was conducted on 188 clients selected randomly at informal markets. RESULTS: 26.6% (32/119) of raw milk samples taken directly from the cow’s udders, 28.6% (4/14) mixture milk of shepherd and 41.2% (7/17) of retailer pooled milk were contaminated by B. cereus. Regarding limits of acceptability, 28.6% (2/7) of retailer pooled milk samples met the standards, 28.6% (2/7) presented a potential risk of disease and 42.8% (3/7) posed a real risk of foodborne poisoning. The sources of contamination of milk by B. cereus were, by decreasing order of importance, the udder (73/113), the water (3/5), the environment (9/16), the milk vendor containers (7/17), the hands of the milker(s) (9/22) and the utensils (4/14). All B.cereus strains (88 strains) isolated were virulent and harbored at least one of the virulence genes hblA, hblC, hblD, nheA, nheB, nheC, bceT and cytK-2. The most frequent virulence genes were hblD (79/88), cytK-2 (79/88), nheC (65/88) and hblC (60/88), all involved in the aetiology of diarrheal syndromes. Among milk consumer’s respondents, 12.8% (24/188) reported episodes of symptoms including diarrhea (19/37), fever (5/37), bloating stomach (4/37), vomiting (3/37) and nausea (1/37). Severe cases requiring a stay of one to three days in hospital were reported by 12.5% (3/24) of those infected. SUMMARY: The probability of consuming milk contaminated by B. cereus was 22.2%. The occurrence of foodborne diseases was significantly related (p < 0.05) to the consumption of unpasteurized milk (Relative Risk (RR): 2.6, 95% CI 1.07 - 6.22). Milk quality could be improved by the introduction of good hygiene practices such as water quality, utensil washing and milk pasteurization. Awareness of stakeholders in the informal dairy sector is also crucial to reduce the risk of infection for the consumer.